2001
DOI: 10.1152/ajpendo.2001.280.1.e150
|View full text |Cite
|
Sign up to set email alerts
|

ANG II is required for optimal overload-induced skeletal muscle hypertrophy

Abstract: ANG II mediates the hypertrophic response of overloaded cardiac muscle, likely via the ANG II type 1 (AT(1)) receptor. To examine the potential role of ANG II in overload-induced skeletal muscle hypertrophy, plantaris and/or soleus muscle overload was produced in female Sprague-Dawley rats (225-250 g) by the bilateral surgical ablation of either the synergistic gastrocnemius muscle (experiment 1) or both the gastrocnemius and plantaris muscles (experiment 2). In experiment 1 (n = 10/group), inhibiting endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
3
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 41 publications
10
98
3
3
Order By: Relevance
“…Previous data regarding the role of Ang II in the control of skeletal muscle mass are controversial. Ang II has been shown to promote muscle atrophy (15); nevertheless, other studies have reported that Ang II induces skeletal muscle hypertrophy associated with strength gain (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Previous data regarding the role of Ang II in the control of skeletal muscle mass are controversial. Ang II has been shown to promote muscle atrophy (15); nevertheless, other studies have reported that Ang II induces skeletal muscle hypertrophy associated with strength gain (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…The primary role of ACE in the renin-angiotensin system is to convert angiotensin I into angiotensin II (Rigat et al 1990), which not only acts as a vasoconstrictor but also regulates smooth (Berk et al 1989;Geisterfer et al 1988) and cardiac muscle growth (Sadoshima et al 1993;Ishigai et al 1997). ACE inhibitors have been shown to inhibit hypertrophy in overloaded muscle, which also suggests a role for angiotensin II in skeletal muscle hypertrophy (Gordon et al 2001;Westerkamp and Gordon 2005).…”
Section: Genotype-phenotype Association Studiesmentioning
confidence: 98%
“…Angiotensin II is a mediator of the hypertrophic response to mechanical loading in rodent muscle (28,29) . The potential synergistic actions of angiotensin II in combination with mechanical loading provides a mechanism by which the previously observed (16,17) greater increases in strength following resistance training in subjects with the D allele may have occurred.…”
Section: Effect Of Training On Physical Functionmentioning
confidence: 99%